2001
DOI: 10.1289/ehp.01109557
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth and length of gestation in relation to prenatal exposure to environmental tobacco smoke assessed by hair nicotine concentration.

Abstract: We assessed the effects of prenatal exposure to environmental tobacco smoke on fetal growth and length of gestation. The study population consisted of 389 nonsmoking women who were selected from a population-based study in southeast Finland on the basis of questionnaire information after delivery (response rate 94%). The final exposure assessment was based on nicotine concentration of maternal hair sampled after the delivery, which measures exposure during the past 2 months (i.e., the third trimester). The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 37 publications
4
69
1
1
Order By: Relevance
“…Similar to this study, many others reported a significant association between SHS and premature birth [12,13,14,15,16]. …”
Section: Ets and Health Effects In Neonatal And Paediatric Populatsupporting
confidence: 90%
“…Similar to this study, many others reported a significant association between SHS and premature birth [12,13,14,15,16]. …”
Section: Ets and Health Effects In Neonatal And Paediatric Populatsupporting
confidence: 90%
“…Indeed, there is compelling evidence from epidemiologic studies of widespread contaminants such as lead, tobacco, and PCBs that human studies are essential to ensure that children are not harmed by low levels of exposure [11,12,13,14,15,16,17,18,19,20,21,22, 23,24,25,26,27,28,29,30,31,32,33,34,35, 36,37,38,39,40]. …”
Section: Limitations Of Existing Animal Tests For Dntmentioning
confidence: 99%
“…Over the past three decades, researchers have found that remarkably low-level exposures to these toxins are linked with less overt symptoms of toxicity—intellectual impairments, behavioral problems, spontaneous abortions, or preterm births [6,7,8,9,10,11,12,13,14, 15,16,17,18,19,20,21,22,23,24,25,26,27, 28,29,30,31,32,33,34,35,36,37,38,39,40]. Moreover, there is emerging evidence that decrements in intellectual abilities and low birth weight linked with lead or tobacco are, for a given increment of exposure, greater at lower levels than those found at higher levels [10,41,42,43].…”
mentioning
confidence: 99%
“…In a Finnish study of nonsmoking women, the risk of preterm birth was dose-related to self-reported prenatal maternal ETS exposure intensity and maternal hair nicotine levels [13]. Glutathione-S-transferase (GST) enzymes detoxify many chemicals, including polycyclic aromatic hydrocarbons and certain other toxicants present in tobacco smoke.…”
Section: Case Studiesmentioning
confidence: 99%